Impact of apheresis automation on procedure quality and predictability of CD34+ cell yield. Issue 4 (23rd March 2018) - Besson, Nelly; Topholm Bruun, Mie; Stauffer Larsen, Thomas; Nielsen, Christian
Abstract: Success of peripheral blood stem cell (PBSC) collections depends on patient biological parameters and stable apheresis device performance. We investigated product quality and factors influencing main apheresis procedure outcomes including CD34 + collection efficiency (CE), product volume or platelet CE. We also assessed different CD34 + cell yield prediction algorithms. Autologous PBSC collections by Spectra Optia from myeloma and lymphoma patients were analyzed. Complete blood count (CBC) from patient preprocedure and from collected products were assessed. (1) Product yield was calculated, (2) Product CBC was correlated with patient preprocedure variables, and (3) Predictions of CD34 + yields based on (a) product CD34 + cell concentration in samples after two or four chamber flushes or (b) traditional CE2 benchmark, were compared. 62 procedures in 41 patients were analyzed. 84% of all procedures were run without operator intervention. Median CD34 + CE2 was 56.9% (48.8%‐65.2%) and quite stable irrespective of patient conditions, with minor influence from patient white blood cell (WBC) precounts ( r s = –.47; P < .001). Platelet loss correlated with WBC precount ( r s = .46; P < .001), product volume ( r s = .71; P < .0001) and number of chambers collected ( r s = .72; P < .0001). CD34 + cell yield was better predicted based on (a) product CD34 + cell concentration from samples after 2 and 4 chamber flushes, respectively ( r s = .969; P < .0001 and r s = .9648; P < .0001) than based on (b) CE2 formula ( r s = .8262, P < .0001). Spectra Optia provides good quality PBSC products with stable and predictable yield regardless of starting conditions. CD34 + sampling of product after few chamber flushes could be used to predict CD34 + yield.